2000
DOI: 10.1136/gut.46.3.367
|View full text |Cite
|
Sign up to set email alerts
|

Defective hMSH2/hMLH1 protein expression is seen infrequently in ulcerative colitis associated colorectal cancers

Abstract: Background-Ulcerative colitis is associated with an increased risk of colorectal cancer above that of the normal population. The relative risk correlates with the extent and duration of the disease but the genetic basis of ulcerative colitis associated cancer risk is not known. Aims-To assess the prevalence of microsatellite instability and mismatch repair gene abnormalities in ulcerative colitis associated colorectal cancer. Patients-Forty six patients with colorectal cancer, with a previous histological diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 15 publications
2
20
1
Order By: Relevance
“…One study reported 6 of 13 samples with high MSI as having hMLH1 hypermethylation (6). Unlike the findings in hereditary nonpolyposis colon cancer, however, other studies found little evidence for mismatch repair defects as a cause of MSI in UC (7,8). This raises the possibility that mechanisms other than mismatch repair defects exist.…”
Section: Introductioncontrasting
confidence: 50%
“…One study reported 6 of 13 samples with high MSI as having hMLH1 hypermethylation (6). Unlike the findings in hereditary nonpolyposis colon cancer, however, other studies found little evidence for mismatch repair defects as a cause of MSI in UC (7,8). This raises the possibility that mechanisms other than mismatch repair defects exist.…”
Section: Introductioncontrasting
confidence: 50%
“…27 However, it is only rarely involved in this setting: Cawkwell et al found neither MSI by PCR nor loss of hMLH1 and hMSH2 expression among 33 colorectal carcinomas complicating ulcerative colitis. 28 MSI also seems to be very unusual in cancers complicating Crohn's disease, even rarer than in those occurring in ulcerative colitis. 29 However, it should be noted that these studies only included colorectal carcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…MSI tends to occur in a subset of about 10% to 15% of IBD tumors that retain their diploid chromosome number (ie, have a low level of CIN), and it was suggested that this subtype may exhibit a genetic predisposition towards MSI, perhaps as a consequence of mismatch repair gene mutation (an HNPCC variant) [41] or saturation as a consequence of increased oxidative stress [42]. Gene mutation is unlikely as low level MSI was not associated with any loss of expression of hMSH2 or hMLH1 protein in UC [43]. The frequency of MSI in acutely inflamed tissue suggests that mismatch repair mechanism saturation in inflammation is possible, but the low level of MSI compared with the high frequency of CIN seen in IBD-associated tumors suggests that MSI is not essential for carcinogenesis to occur in IBD.…”
Section: Microsatellite Instabilitymentioning
confidence: 99%